PENGARUH MODEL TWO STAY TWO STRAY TERHADAP HASIL BELAJAR TEMATIK SISWA DI SEKOLAH DASAR - Mardianto, Mardianto; Marli, Suhardi; Kresnadi, Hery (Jurnal Pendidikan dan Pembelajaran Khatulistiwa, 2019)
AbstractThe purpose of this research is to analyze the influence of Two Stay Two Stray model on the results of the student thematic learning outcomes of State Elementary School 06 Mensere District Sambas. The research method used is experimentation, form Quasi Experimental type non equivalent group design. The research population is all student of fourth grade state elementary School 06 Mensere District Sambas totalling 52 students. Sampling techniques using purposive sampling. The technique used is measuring techniques. The Data collection tool is a question of multiple choice tests. The data analysis result is, the average post-test control class score is 61.93 and the experiment is 67.54. Based on the results of T-test calculation obtained Tcount 3.594 > Ttable 1.678, then Ha accepted. This indicates that there is a difference in the student learning outcomes with the experiment class. Calculation of effect size is 0.78 with moderate criteria. The conclusion of this research is that there is the influence of Two Stay Two Stray models on the outcome of thematic learning results students fourth grade State Elementary School 06 Mensere Sambas in the medium category.Â Keywords: Learning Model for Two Stay Two Stray, learning outcomes, thematic